Prevalence of Voluntary Counseling and Testing Utilization and Its Associated Factors among Bahirdar University Students. (3rd July 2014) - Fikadie, Getachew; Bedimo, Melkamu; Alamrew, Zelalem
Abstract : Background. In Ethiopia university students are among the most sexually active and high HIV risk young population group but unfortunately VCT uptake was low (35%–38%) among this group. Examining the factors contributing to VCT uptake is vital to facilitate HIV prevention and control efforts. Objective. To assess the prevalence of voluntary counseling and testing utilization and its associated factors among Bahirdar University students in April 2012. Methods. Cross-sectional study was conducted in April 2012, among Bahirdar University students. A multistage sampling procedure was used to select 801 students. Data were collected using pretested self-administered questionnaire and analyzed by using SPSS version-16. Results. 772 students (79.7% males) participated in the study. The mean age of the respondents' was 21.3. From all respondents 37.8% of the study participants had undergone HIV test. Different variables showed significant association with VCT uptake. Conclusion. The major factors identified for increased VCT service utilization were having a friend who got VCT, having discussion about HIV/AIDS with family, origin of residence, year of study, and having boy- or girlfriend. Therefore, actions targeting these predictors are necessary to effectively enhance the use of the VCT services utilization among students.